قراءة ابن القيم الجوزية لآراء سيبويه- كتاب إرشاد السالك إلى حل ألفية ابن مالك (Journal of the College of Basic Education, 2026)
This research examines and investigates the views of Sibawayh (d. 181 AH) in one of the commentaries on Ibn Malik's (d. 672 AH) Alfiyyah, the commentary by Ibn al-Qayyim al-Jawziyyah (d. 767 AH), entitled "Guidance for the Traveler to Solve Ibn Malik's Alfiyyah." It compares these views with what is contained in Sibawayh's book. The aim is to document and verify what is attributed to Sibawayh in this commentary, to understand the commentator's understanding of Sibawayh's doctrine, and to verify the correctness of his understanding and the accuracy of the transmission. It has been shown that a number of opinions contradicted the author's intentions, sometimes due to misunderstanding and other times to intermediary transmission. However, most opinions were consistent with what was stated in the book.